2022
DOI: 10.7717/peerj-cs.1187
|View full text |Cite
|
Sign up to set email alerts
|

Research on air quality prediction based on improved long short-term memory network algorithm

Abstract: Air quality is changing due to the influence of industry, agriculture, people’s living activities and other factors. Traditional machine learning methods generally do not consider the time series of the data itself and cannot handle long-range dependencies, thus ignoring information relevant to the predicted items and affecting the accuracy of air quality predictions. Therefore, an attention mechanism is introduced based on the long short term memory network model (LSTM), which attenuates unimportant informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This novel gating system enhanced information discernment and enabled effective simulation of multiple inputs. As supported by research studies, , the LSTM model exhibited better performance in processing time-series problems. Furthermore, these findings indicated that the LSTM model is better equipped to capture the complex spatiotemporal variability associated with various PM metrics …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This novel gating system enhanced information discernment and enabled effective simulation of multiple inputs. As supported by research studies, , the LSTM model exhibited better performance in processing time-series problems. Furthermore, these findings indicated that the LSTM model is better equipped to capture the complex spatiotemporal variability associated with various PM metrics …”
Section: Resultsmentioning
confidence: 99%
“…Menares et al (2021) employed both a deep feedforward neural network (DFFNN) and LSTM models to forecast the PM 2.5 concentration value, with the LSTM model outperforming the DFFNN model and achieving the highest accuracy of 0.87 . While these models enhance the precision of predictions to varying extents, they face a common limitation: as the length of the time series grows, data points that are further away from the present information become increasingly disregarded . This can lead to a loss of valuable information that may be crucial for accurate forecasting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse modelling technique, based on multi-sensor measurement, has steadily emerged as a new solution with development of CAD film as well as television scenes. A thorough overview of the fundamentals, benefits, and uses of this technology in the creation of motion pictures and television shows was given by author [15]. Reverse engineering techniques are used in CAD film as well as television scene reverse modelling based on multisensor measurement, which transforms sensor data into a 3D CAD model.…”
Section: Related Workmentioning
confidence: 99%